Inverting social innovation to transform health system responses to climate change adaptation and mitigation in the global south - Katapally, Tarun R.; Bhawra, Jasmin (Frontiers in Public Health, 2024)
Systems thinking aims to understand and solve complex problems that cut across sectorsan approach that requires accurate, timely, and multisectoral data. Citizen-driven big data can advance systems thinking, considering the widespread use of digital devices. Using digital platforms, data from these devices can transform health systems to: 1) Predict and prevent global health crises;and 2) Respond rapidly to emerging crises by providing citizens with real-time support. For example, citizens can obtain real-time support to help public health risks via a digital app, which can predict evolving risks. These big data can be aggregated and visualized on digital dashboards, which can provide decision-makers advanced data analytics to facilitate jurisdiction-level rapid responses to evolving climate change impacts (e.g., direct public health crisis communication). In the context of climate change, digital platforms can strengthen rapid responses by integrating information across systems (e.g., food, health, and social services) via citizen big data. More importantly, these big data can be used for rapid decision-makinga paradigm-changing approach that can invert social innovation, which we define as co-conceptualizing societal solutions with vulnerable communities to improve economic development, with a focus on community wellbeing. However, to foster equitable and inclusive digital partnerships which invert social innovation, it is critical to avoid top-down approaches that sometimes result when researchers in the global north and south collaborate. Equitable global south-north partnerships can be built by combining digital citizen science and community-based participatory research to ethically leverage citizen-driven big data for rapid responses across international jurisdictions.